The needs of older patients in hospital care: a scoping review - Bláhová, Hana; Bártová, Alžběta; Dostálová, Vladimíra; Holmerová, Iva (Aging Clinical and Experimental Research, 2021)
BACKGROUND: Research into care for older patients in the hospital environment has become an increasingly valuable source of information, as it gives feedback on the quality of hospital care provided. The aim of this study is to provide a comprehensive overview of the self-reported needs of older people in hospital care. METHODS: The scoping review was conducted by searching the following databases: Medline, Web of Science, ProQuest Central, Scopus, Cinahl, PsycINFO and Summon. RESULTS: The search identified articles focusing on older people in hospital care. The majority of these articles address the system and quality of care for seniors at a somewhat general and theoretical level. Met and unmet needs were assessed by a variety of test methods focusing mainly on medical issues (e.g., Mini-Nutritional Assessment, ADLs-activities of daily living, Abbey Pain Scale) and mostly from the perspective of hospital staff, carers and relatives. Only 15 articles used assessments based on information and opinions obtained from the seniors themseAbstract_Paralves (self-reported needs). A thematic analysis revealed seven main themes: conduct and care in emergency departments, dignity, nutritional care, satisfaction of patients' needs, pain, caring with respect, decision-making and spiritual needs. CONCLUSION/DISCUSSION: The results of this scoping review suggest that more attention should be focused on information acquired from the patients themselves, as it is only the patient, however, old or frail, who can offer an accurate perspective on met or unmet needs and the quality of care provided.
Keywords: Hospitals; Activities of Daily Living; osoby pečující o pacienty; Aged; lidé; činnosti denního života; senioři; nemocnice; Humans; Caregivers